The PEFINDO25 COMPANY CLUSTERIZATION IN GLOBAL RECESSION 2023 USING FINANCIAL RATIOS INDICATORS - Ignatia Thomasita Bau Mau (SEAN Institute, 2023)
The public in general will continue to face the phenomenon of economic recession even though the financial position of the Indonesian state is still strong and stable. To be aware of this situation, it is necessary to make appropriate investment efforts so as to maintain the sustainability of the household financial condition of each community. However, in the midst of issues of economic recession, investors are very wary of investing a certain amount of capital in companies that are on the capital market. Investors tend to look at small companies that have the possibility to invest, but from a fundamental standpoint, these companies must have optimal financial health. The world of capital markets knows the companies included in the Pefindo25 index. These Pefindo25 companies are small and medium-sized companies that are selected with certain criteria as representatives of small companies that have good financial development and have the right financial performance. From this study, an analysis of financial ratios was carried out as an indicator to measure the financial health of companies included in the Pefindo25 index for the period August 2022 to January 2023. The results of measuring financial ratios and clustering with Pseudo-F statistics in the SPSS program show that the company BFI Finance Indonesia Tbk. (BFIN) is a company that has a good level of fulfillment of short-term and long-term obligations, the assets used to carry out operational activities are managed properly and the capital owned by the company can be optimized appropriately for the company's sustainability. BFIN can be the choice of investors to invest some of their capital in the company, amidst the world's unstable economic conditions such as the issues of the 2023 global economic recession.